(3EMJQGa EOGQI bhGYO GdHjGfGJ HGSJNOGe (BMicrosoft SQL server 2000s - (3YeQh(B, (3YfGfjs ((3GdbGgQI(B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B,s, 2004)
(3fXQI YGeI Ydi NGOe (BSQL server 2000 - (3JLgjR GSJNOGe NGOe (BSQL server 2000 - (3age bhGYO GdHjGfGJ GdNGUI HGdfXGe hGdeSJNOe(B- (3Jchjf hJgjFI bhGYO GdHjGfGJ GdeSJNOejf(B- (3Jchjf hJgjFI bhGYO GdHjGfGJ(B- (3fTQ bGYOI GdHjGfGJ(B- (3JWhjQ GSJQGJjLjI GSJQLGY GdHjGfGJ(B- (3GdfSN GdEMJjGWj hGdESJQLGY aj NGOe (BSQL.s
Keywords: Microsoft SQL server 2000; (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs